Environmental Citizenship from the Perspective of University Staff at Ain Shams University - Reham R. Abdelaal (Sultan Qaboos University, 2017)
The study aimed at identifying the dimensions of environmental citizenship from the perspective of university staff members in Ain Shams University, and its relation with some variables including gender, college (theoretical and practical) and scientific degree. The study was done using the descriptive method, and a questionnaire consisting of 63 items distributed on four dimensions (Environmental Justice -Environmental Rights Environmental Responsibility and participation in environmental decision-making). The researcher checked its validity and reliability and the questionnaire was distributed to a sample consists of 268 University staff Member's. The results of the study showed that there were differences in the average of the degrees of perception of Ain Shams university staff members of dimensions of the environmental citizenship. The dimension of environmental rights came in the first degree, as it reflected a very large degree of perception, followed by both dimensions of environmental responsibility and participation in environmental decision-making, which reflected a large degree of perception, and finally the dimension of environmental justice which reflecteda a medium degree of perception. The study also showed that there no were statistically significant differences related to gender, while there were statistically significant differences at the level of 0.05 related to the variables of college and scientific degree.